EXPLORATION OF HUMAN BEHAVIOR OF WATER-SAVING UNDER CLIMATE CHANGE USING EXPANDED THEORY OF PLANNED BEHAVIOR MODEL - Ho, Fong; Lin, Yaw; Lai, Wen (MATTER: International Journal of Science and Technology, 2016)
In response to the water shortage issue caused by climate change, an extending planned behavior model of environmental concern is applied to explain the household behavior relatedto water conservation in southern Taiwan. Based on the data from the 1678 valid samples using random sampling, an extending planned behavior model to which the variable of environmental concern is added besides the original variables in the theory of planned behavior (TPB) model. It was also verified to properly explain the household behavior related to water conservation for climate change mitigation. Furthermore, the exploratory factor analysis was successfully extracted into the three factors in environmental concern and the four factors in water conservation behavior. The results indicate that the extended TPB model including environmental concern can increase the explanatory power of the original one. In addition to the attitudes, perceived behavioral control and subjective norm, people's environmental concerns may reduce the impact on global warming and climate change. As a result, people's intentions to engage in water savings and carbon reduction behavio rs can be expected to mitigate climate change problems.